PENGEMBANGAN CABAI KATOKKON (Capsicum annuum L. var. sinensis) DI LUAR HABITAT ASLINYA - Ibrahim, Bakhtiar; Numba, Sudirman; Hazisah, Nur (Percetakan Umi Toaha Makassar, 2024)
This research aims to develop Katokkon chilies outside their natural habitat with different environmental conditions. Increase soil fertility levels in areas with low fertility levels by adding manure and NPK fertilizer. The study used a two-factor randomized block design (RBD): NPK fertilizer and cow manure. NPK fertilizer consisted of 2 grams, 4 grams, 6 grams per 10 kg of soil, and control (without NPK fertilizer). Cow manure treatment consisted of 0.5 kg, 1 kg, and 1.5 kg per 10 kg of soil and without cow manure (control). Each treatment was repeated 3 times and consisted of 3 plants for each observation unit. The research results show that developing katokkon chili plants outside their natural habitat is still possible. Providing 0.5 kg of cow manure had the best effect on the parameters of plant height, fruit weight, and production of Katokkon chili plants. Adding 2 g NPK fertilizer provided the best growth in terms of plant height, fruit weight, and production parameters. However, the addition of 6 g NPK fertilizer affected the productive branch parameters of Katokkon chili plants. There was a real interaction between 0.5 kg cow manure and the addition of 2 g NPK fertilizer on the parameters of plant height, fruit weight per plant, and production of Katokkon chili plants